Rede social de apoio no cuidado às pessoas com estomia: implicações para a enfermagem - Carvalho, Sandra Ost Rodrigues Martins (2012)
It is a qualitative, descriptive kind research, which had by objective to understand the social net that takes care people with stomia registred in the Municipal Program of Stomiad in a smll town of RS. The subjects were six individuals with intestinal ostomy registered on that Program. For data collection was used semi-structured interview and observation. The analysis was made by theme content analysis, which unfolds into three stages: the Pre- Analysis, the Material Exploration and the Treatment of Obtained Results and Interpretation. Were respected all the ethical aspects of researches with human beings, according to the Resolution 196/96, from National Health Council. The categories that came from data analysis are described and discussed in three articles that make the essence of the present work: Article 1: Support Social Nets of Ostomy Persons Care: Bibliographic Revision; Article 2: Even I Knew I Had so Many People For Me: Support Social Net For Persons With Ostomy; Article 3: With a Little Care We Go Forward: Living Histories From Persons With Ostomy. The results of article 1 happende by analysis of 11 articles of the literature, from those came the categories: Family support, Support of group of people with ostomys, Support realized by nurse and other professionals of health. The estudies qualitative werw thw most frequent and the cientific production of nursing numerical small. We can conclude that the know ledge about the social net of support is important to take care people with ostomys. The article 2 shows that the social net of support of people of ostomy was composed by family, friend, neigbours, workmates and professional of health. For this reason, it was realized how important is a social net strong among people with ostomy, because it helps a essencial support to its realization and survive with a new life condition. From article 3 came 3 categories: I am very well care, it s a little diffent of my life and it is necessary to go on, we can not stop. We feel that it s essencial to understand the ways of care that permeate ways of lives of people with ostomy as well the changes that happen in their lives and how they face these situations. We believe tha that this knowledge can aproch the nurse to the reality of these people lives, instrumentalizing to a qualified and resolutive assistency.